A retrospective study of blunt trauma abdomen in a tertiary center in central India: evaluation, management and outcome - Sisodiya, Sanjay; Malpani, Prateek (International Surgery Journal, 2020)
Background: Blunt abdominal trauma is fairly common emergency and it is one of the important components of polytrauma. It requires high degree of suspicion, investigation and management. Inspite of improved imaging techniques leading to early recognition it is still associated with high morbidity and mortality. Trauma is the leading cause of blunt abdominal injury. This aim of the study was to find etiology, early diagnosis and management of patients with blunt abdominal trauma. Methods: This a retrospective study conducted in Gandhi medical college, Bhopal in which 90 cases of blunt abdominal trauma presented to emergency and outpatient department were included in the study duration of January 2019 to December 2019. Results: Motor vehicle accident was the most common mode of injury. Liver being the most common visceral organ injured while the most common surgery performed was the repair or resection and anastomosis of hollow viscous perforation. Rib fracture was the most common extra abdominal injury seen in 17.7% cases. Mortality rate was 5.5%. Most of the liver, spleen and renal injuries can be managed non-operatively whereas hollow viscous injury needs laparotomy. Conclusions: The result of present study is similar to other studies. Rapid diagnosis, early and timely referral, adequate and trained staff, close and careful monitoring, early wise and skilled decision to go for operative or non-operative management can help save many lives.